Anna's crossing [large type] : an Amish beginnings novel - Fisher, Suzanne Woods (Fisher, Suzanne Woods. Amish beginnings novel, 2015)
When Anna Konig first meets Bairn, the Scottish ship carpenter of the "Charming Nancy," their encounter is anything but pleasant. Anna is on the ship only to ensure the safe arrival of her loved ones to the New World. Hardened by years of living at sea, Bairn resents toting these naive farmers -- dubbed "Peculiars" by deckhands -- across the ocean. As delays, storms, illness, and diminishing provisions afflict crew and passengers alike, Bairn finds himself drawn to Anna's serene nature. For her part, Anna can't seem to stay below deck and far away from the aloof ship's carpenter, despite warnings. When an act of sacrifice leaves Anna in a perilous situation, Bairn discovers he may not have left his faith as firmly in the past as he thought. But has the revelation come too late?